Cataclysms and Currencies : Does the Exchange Rate Regime Matter for Real Shocks? - Ramcharan, Rodney (IMF Working Papers; Working Paper, 2005)
Does the choice of exchange rate regime affect the way an economy's adjustment to real shocks? Exploiting the randomness of natural shocks, this paper assesses empirically the often contrasting answers found in the theoretical literature. The evidence supports key themes in this literature, and points to an important tradeoff between regimes. First, adverse natural shocks are associated with both higher investment and foreign direct investment (FDI) only in developing countries with fixed rate regimes. Second, over a 24-month horizon, growth rebounds earlier in flexible rate regimes. Third, in the long run, more adverse shocks are associated with higher growth and investment only in predominantly fixed regimes. Thus, while claims of faster adjustment to real shocks under flexible rate arrangements have merit, so does the idea that exchange rate variability can impede investment. And the benefits from faster adjustment may come at the cost of foregoing the long run productivity benefits embodied in the larger investment response in fixed rate regimes.